Intergenerational locative play : augmenting family - Saker, Michael; Evans, Leighton (Emerald Publishing Limited, 2021)
Intergenerational Locative Play: Augmenting Family examines the social, spatial and physical impact of the hybrid reality game (HRG) Pokémon Go on the relationship between parents and their children. The ubiquity of digital media correlates with a mounting body of work that considers the part digital technologies, such as video games, play in the lives of children. Consequently, commentators have deliberated the effects of rising levels of screen time and the association of this trend with antisocial behaviour, mental health-related problems, and the interference of family life. Yet, recent studies have demonstrated that the intergenerational play of video games can in fact strengthen familial connections by facilitating communication between adults, and children, and allowing adolescents to experiment with a range of roles. Research on intergeneration play, however, has tended to focus on video games played within the domestic sphere. In contrast, Locative games, such as Pokémon Go involve players physically interacting and moving through their surroundings. Through an original study of Pokémon Go this book extends developing research on intergenerational play to the field of locative games.